Why Depend on Others? Why Not Thinking of Ours? A Methodological Approach to Conceptualization in Social Science Research - Wijesinghe, M.A.S. (IRCHSS-2018 and Faculty of Humanities and Social Sciences, University of Sri Jayewardenepura, 2018)
It is so clear that many of our researches depend on others’ concepts and knowledge. It is the influence of scientific positivism into our research, as we always try to frame the research within a conceptualized frame developed from others’ knowledge addressed in literature. There is no argument that others’ knowledge is essential to be a good academic and scientific scholar, as the quality of our research is inevitably be judged in relation to other researchers’ and scientists’ work. But it is timely to re-think the extent to which such knowledge and concepts, particularly designed based on the literature, are relevant and applicable to different social and cultural structures. It is also timely to re-think whether we are ready to rely any further on such literature-based knowledge which could be or could not always be practicable and applied. On the other hand, is there any possibility of applying the concept of universalism emphasized by the scientific positivism to every society and culture neglecting their diversity? If so, have we so far thought of designing our own concepts or developing our own methodology to understand any of the knowledge belonging to us? It is correct to mention here that it is very rare in our literature of generating our own set of indigenous knowledge or suggesting an approach to generate such knowledge. Therefore, the objective of this plenary speech is to emphasize a research approach as one of the essential methodological approaches to generate knowledge for any given society or culture. Methodologically, this is a conceptual paper that emphasizes an approach to generate concepts or knowledge particularly by applying signs, objects and concepts as the instruments to generate knowledge. As the outcome, the practice of this approach by the scientists and researchers to conceptualize knowledge from ground level is expected.
Keywords: Concepts; Knowledge; Objects; Scientific positivism; Signs